KEBIJAKAN DI ERA PEMERINTAHAN JOKO WIDODO DAN JUSUF KALLA (PERSPEKTIF POLITIK HUKUM DAN AGRARIA) - NI LUH ARININGSIH SARI; I WAYAN SUWANDA (Universitas Mahasaraswati Mataram, 2019)
The political development of agrarian law in Indonesia is inseparable from the policies of the ruling government in each period of government. The period of development can be divided into 4 four periods, namely the colonial period, the Soekarno administration, the Soeharto era and the Reformation period. After the reformation, several presidential changes, namely Habibie, Gusdur, Megawati and Susilo Bambang Yudoyono, policies on the regulation of natural resources and resources are not clearly seen as the implementation of TAP MPR No. IX / 2001. Discourse related to changes in diagrammatic arrangements has been discussed but not implemented optimally. At present the Indonesian government is being led by President Joko Widodo trying to implement changes to the political law of diagramming in Indonesia